1996
DOI: 10.1111/j.1399-6576.1996.tb04490.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditions to optimise the reversal action of neostigmine upon a vecuronium‐induced neuromuscular block

Abstract: To optimise the reversal action of neostigmine in order to obtain the highest neuromuscular transmission recovery (0.9 TOF ratio and RF100Hz) during a vecuronium-induced neuromuscular block, the 40 micrograms/kg dose has to be given at 25 to 50% recovery of TH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
6
20
0
2
Order By: Relevance
“…To optimize the reversal achieved with acetylcholinesterase inhibitors, some spontaneous recovery of neuromuscular function is required before administration [8], and our study confirms this. This means that clinicians may be unable to maintain profound block to the end of surgery without the penalty of the time required for spontaneous recovery prior to acetylcholinesterase inhibitor administration, as well as the fear of residual block in the recovery room in a patient who has not adequately recovered from the block.…”
Section: Discussionsupporting
confidence: 78%
“…To optimize the reversal achieved with acetylcholinesterase inhibitors, some spontaneous recovery of neuromuscular function is required before administration [8], and our study confirms this. This means that clinicians may be unable to maintain profound block to the end of surgery without the penalty of the time required for spontaneous recovery prior to acetylcholinesterase inhibitor administration, as well as the fear of residual block in the recovery room in a patient who has not adequately recovered from the block.…”
Section: Discussionsupporting
confidence: 78%
“…Measurements of T1 ⁄ control and train-of-four ratio (TOFR) were taken 3 min, 6 min, 9 min, 12 min and 15 min after the administration of neostigmine, and the values for the two groups were compared. It has been shown that 15 min after the administration of neostigmine at a T1 ⁄ control value of 0.25, TOFR often does not return to 0.9 [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the amount of acetylcholine released from nerve endings may decrease in diabetic patients. Anticholinesterases increase the release of acetylcholine, resulting in an increased postjunctional endplate potential [17]. As the number of axons and therefore nerve endings decrease in diabetics, the release of acetylcholine provoked by anticholinesterase should also be decreased.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain optimal reversal as measured by a TOF ratio of 0.9 during a vecuronium-induced neuromuscular block, a dose of neostigmine 40 µg/kg was required at 25-50% recovery of twitch height. 26 Administration of increasing and multiple doses of acetylcholinesterase inhibitors does not confer linear pharmacologic effects on reversal. Neostigmine, pyridostigmine, and edrophonium were equally effective at reversal of blockade as measured by TOF stimulation.…”
Section: Onset Of Acetylcholinesterase Inhibitorsmentioning
confidence: 99%